Algorithm of deformed state modeling and determination of metall constructions durability in radiation streams - Матченко, Т.І.; Радецька, Я.В.; Матченко, П.Т. (Proceedings of National Aviation University (archive), 2005)
There is given algorithm of calculation with the help of finite elements method, and determination of остаточный resource of metal constructions durability under influence of thermal and radiation streams.